The Effect of Work Motivation and Commitment on Teacher Performance - Kasyful Anwar; Rahmi Widyanti; Rabiatul Adawiah; Unut Triyuliadi (GoAcademica Research & Publishing, 2021)
Teacher performance needs to be continuously improved because it affects the quality of graduates and the quality of education. It is necessary to conduct research related to what factors can affect teacher performance to improve teacher performance. This study aims to analyze the effect of motivation and work commitment on teacher performance. This study uses a quantitative approach. The sampling technique used in this research is saturated sampling. All members of the population, amounting to 43 people, are used as samples. Data collection was done by using a questionnaire technique. Before the instrument is used, the first instrument is tested to determine its validity and reliability. Technical analysis of the data using simple linear regression test and multiple linear regression using the SPSS version 22 application. From the research results, it is known that (1) motivation has a significant positive effect on teacher performance by 36.1%; (2) commitment has a significant positive effect on teacher performance by 41.0%; (3) simultaneously work motivation and commitment have a positive effect on teacher performance by 50.7%. The conclusion is that the two variables, individually or together, are a determining factor in improving teacher performance.